Application of EXAFS with a bent crystal analyzer to study the pH-dependent microstructure of Eu(III) onto birnessite. Issue 1 (February 2018) - Dong, Lijia; Liao, Qing; Linghu, Wensheng; Huang, Yuying; Shen, Runpu; Alsaedi, Ahmed; Wang, Jin; Hayat, Tasawar; Sheng, Guodong
Highlights: Eu(III) sorption onto δ-MnO2 was dependent on pH but not ionic strength. Inner-sphere surface complexation dominated Eu(III) sorption on δ-MnO2 surface. Retention of Eu(III) on δ-MnO2 is in forms of corner-sharing bidentate species. This work enhances our understanding for the sorption mechanisms of Eu(III). Abstract: Herein, Eu(III) retention mechanism and microstructure on δ-MnO2 as a function of solution pH were studied using both the conditional macroscopic method and molecular-level high resolution EXAFS technique with a bent crystal analyzer. The results suggested that the sorption Eu(III) onto δ-MnO2 was strongly dependent on pH but not on ionic strength, implying the formation of inner-sphere surface complexation for Eu(III) on δ-MnO2 surface. Molecular-level results from EXAFS methods showed that Eu was surrounded by ∼8O atoms in first coordination shell at R Eu-O  ≈ 2.42 Å, and second shell of Mn atoms at R Eu-Mn  ≈ 3.91 Å was found in four sorption samples from different solution pH. All this results reflected the formation of a bidentate surface complex with Eu(III) bonding by corner sharing to MnO6 -octahedron on δ-MnO2 surface. Both the macroscopic findings and microstructure of Eu(III) at the δ-MnO2 -water interface enhance our understanding for the reaction dynamics and states of Eu(III) and related radionuclides in natural environment.